Incidence of clinical diseases and disorders in goats at Bangladesh Livestock Research Institute - Munsi, Md Nuruzzaman; Ershaduzzaman, Md; Akther, Sonia; Rahman, Md Mamunur; Rahman, Md Habibur; Rahman, Mohammad Mojibur (Asian Journal of Medical and Biological Research, 2018)
The current study was performed to determine the incidence and trends of clinical diseases and disorders in Black Bengal and Jamnapari goats in order to design a set of strategies to be applied for the prevention and control of these problems in this farm. A total of 739 Black Bengal and 285 Jamnapari goats at BLRI goat research farm, Savar, Dhaka, Bangladesh were included under this study. The study was performed out during the period from January 2012 to December 2014. Diagnoses and records of clinical diseases and disorders were based on pertinent clinical history, clinical findings and laboratory tests. The major clinical diseases and disorders were determined pneumonia (37.44%), diarrhoea (21.22%), lameness (3.01%), mange (2.99%), malnutrition (2.82%), contagious ecthyma (1.93%) and fever (1.85%). In case of seasons, the highest incidence was found during rainy season (2.26%) followed by winter (5.85%) and summer (4.25%); whereas in respect of age groups, the highest incidence was found in growing goat (26.14%) followed by adults (12.15%) and kids (10.93%). So, we may conclude that although some diseases and disorders occurred in the BLRI sheep research farm, the incidence were not high. In addition, on the basis of these findings measures should be taken for further prevention of such diseases and manifestations. Asian J. Med. Biol. Res. December 2018, 4(4): 351-361